Lineage decisions in the thymus: αβ and γδ T cell lineages - Silva-Santos, Bruno (Henry Stewart Talks, 2021)
Somatic recombination of TCR genes, αβ and γδ T cell differentiation, The pre-TCR, CD4+ or CD8+ αβ T cell lineage?, Determinants of Tconv or Treg T cell development, γδIFN or γδ17 T cell development?